If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + -5 = 3 + -2y Reorder the terms: -5 + 3y = 3 + -2y Solving -5 + 3y = 3 + -2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '2y' to each side of the equation. -5 + 3y + 2y = 3 + -2y + 2y Combine like terms: 3y + 2y = 5y -5 + 5y = 3 + -2y + 2y Combine like terms: -2y + 2y = 0 -5 + 5y = 3 + 0 -5 + 5y = 3 Add '5' to each side of the equation. -5 + 5 + 5y = 3 + 5 Combine like terms: -5 + 5 = 0 0 + 5y = 3 + 5 5y = 3 + 5 Combine like terms: 3 + 5 = 8 5y = 8 Divide each side by '5'. y = 1.6 Simplifying y = 1.6
| y+4=-21 | | x-3(x+1)=9 | | -12x=-4+28 | | 4t+1+4t-7t=6+6 | | 2x+15=2x-3x | | 24(4k+22)=24(4k+24) | | (2+i)+(-7+5i)= | | 7*(-6)*5*(-4)*3*(-2)*1*0= | | 36+104-7x=8x | | -4y+7=-5y+8 | | 1/4s=-5 | | X=19+4y | | 3x^2-2x=8x-8 | | 3f-4-5f=f+4+5 | | 15x^2=100 | | -20n+6(16+16n)=-12(n-8) | | 3y^2=-7-4 | | -21y=-765 | | 3n+18=-24 | | 2x^7/2x^3/13 | | 1/3(9x+5)=5(x-1)-6 | | 4b^2+(-7)b=0 | | 2a+6=a-8 | | f(x)=2x^2-5x-3 | | -3h+4.2=55-11h | | 6+(3x-3)=2 | | 3x+5-3x=4x-2 | | 3x+5-3x=4x-2 | | -10+p/9=-11 | | -9(x+6)=-54 | | 1/5s=2 | | 8x^2-22x-90=0 |